Study the Effect of adding Carboxy Methyl Cellulose Powder to Low Density Polyethylene on Shielding Radiation for the X-ray - Raed M.Shaban; Shaymaa H. J; Wisam A. Radhi; Ziyad T.Almalki; Muzahim M. A (Journal of Kufa-Physics, 2018)
The attenuation measurements of  x-ray of  voltage range (21kv) for hosted polymer material were done using  x-ray unit, in order to extract the effect of adding carboxy methyl cellulose material (CMC) to low density polyethylene on x-ray radiation  attenuation . The linear attenuation coefficient (µl ) was calculated for the voltage range mentioned   above , through linear equations of  the yield of graphic representation between the logarithmic absorption and the sample thickness X(cm). The mass attenuation coefficient (µm ) could also be calculated through the graphic relation between the logarithmic absorption and the equivalent thickness of the sample Xm(gm/cm2 ) such that slope of the graphic relation represents linear the attenuation coefficient or mass attenuation coefficient. The calculated results indicated that the efficiency of prepared material to absorb X-ray and to attenuate it were high. This efficiency change relatively according to the added ratio and on  type of material .This indicate a significant positive result for these adders on the characteristic radiation attenuation of the polymer,1 low density polyethylene.